Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1108/ebhrm-10-2018-0062
|View full text |Cite
|
Sign up to set email alerts
|

The impact of organizational support for employees’ health on organizational commitment, intent to remain and job performance

Abstract: Purpose The purpose of this paper is to examine the relationship between employees’ perceptions of organizational support for employee health (OSEH) and employees’ turnover intention and job performance, with a focus on the possible mediating roles of affective commitment and wellness program participation in these relationships. Design/methodology/approach Data were collected from surveys of employees at a public university that provides employees with a variety of wellness program options. Conditional proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 48 publications
2
11
0
6
Order By: Relevance
“…The empirical finding of this study reveals that POS is directly related to PJS and PJP. In this study, it was found that POS has significant positive direct effect on PJP, the finding is consistent with past empirical findings of Na-Nan, Saribut and Sanamthong [9], Xiu, Dauner and McIntosh [10], Du et al [11], Byrne and Hochwarter [12], Biswakarma [13], Burmeister and Deller [14], Yaakobi and Weisberg [15], Wickramasinghe and Wickramasinghe [8], Hakkak, Gashti, and Nawaser [1], Guan, Sun, Hou, Zhao, and Luan [17], Armeli, Eisenberger, Fasolo, and Lynch [16], Eisenberger, Huntington, and Hutchison [6], where it was mentioned that the critical role in the employees' performance, they are to be sufficiently supported by the organization [13]. Burmeister and Deller [14], Yaakobi and Weisberg [15] concluded that perceived environmental support and knowledge sharing as the main factors which can heightened active job performance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The empirical finding of this study reveals that POS is directly related to PJS and PJP. In this study, it was found that POS has significant positive direct effect on PJP, the finding is consistent with past empirical findings of Na-Nan, Saribut and Sanamthong [9], Xiu, Dauner and McIntosh [10], Du et al [11], Byrne and Hochwarter [12], Biswakarma [13], Burmeister and Deller [14], Yaakobi and Weisberg [15], Wickramasinghe and Wickramasinghe [8], Hakkak, Gashti, and Nawaser [1], Guan, Sun, Hou, Zhao, and Luan [17], Armeli, Eisenberger, Fasolo, and Lynch [16], Eisenberger, Huntington, and Hutchison [6], where it was mentioned that the critical role in the employees' performance, they are to be sufficiently supported by the organization [13]. Burmeister and Deller [14], Yaakobi and Weisberg [15] concluded that perceived environmental support and knowledge sharing as the main factors which can heightened active job performance.…”
Section: Discussionsupporting
confidence: 92%
“…Na-Nan, Saribut and Sanamthong [9] study found that perceived environmental support and knowledge sharing positively influenced employee job performance of 344 admins working at SMEs in Central Thailand. Xiu, Dauner and McIntosh [10] in a study of 297 employees working at a public university in the US Midwest showed a result that employees' perceptions of organizational support for employee health positively related to both turnover intention and job performance. A study by Du et al [11] of 594 employees in 3 manufacturing companies in Northeast China demonstrated the direct positive influence of perceived organizational support on in-role performance.…”
Section: Perceived Organizational Support and Perceived Job Performancementioning
confidence: 99%
“…Fourth, the study found that OC plays a fully mediator role on the effect of OS on TI, which is in accordance with prior studies in the literature [102][103][104]168]. According to the findings of this study, organizations' support for their employees during challenging times both positively impacts OC and decreases their TI as a result of such interaction.…”
Section: Discussionsupporting
confidence: 91%
“…Rhoades and Eisenberger [ 51 ] revealed in their study that employees’ organizational commitment improves in organizations with high levels of OS, which negatively affects TI. OS has also been proven to be effective on TI via OC by Albalawi et al [ 102 ] in a study which was conducted with SME employees, Nadeem et al [ 103 ] in a study with bank employees, and Xiu et al [ 104 ] with a study with employees at a public university. Chew and Wong [ 105 ] also found in their study in Malaysia that OS is both related to OC and TI.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who identify with the organization or have a sense of belonging and positively commit to the organization will perform better (Suharnomo & Hashim, 2019). Individuals in the workplace who feel more support from the organization tend to show emotional commitment to the organization, which in turn is more to contribute to improved job performance (Xiu et al, 2019). Decreasing the likelihood of employee turnover and enhancing job performance are signs of an organizational commitment to its employees (Ahmad et al, 2021).…”
Section: Organizational Commitment and Job Performancementioning
confidence: 99%